Location economics theoretical underpinnings and applications - Greenhut, Melvin L. 1921- (Economists of the twentieth century, 1995)
These essays make a major contribution by enabling the reader to appreciate the important developments that have taken place over recent years in location economics. Location Economics and its companion volume, Spatial Microeconomics, will be welcomed by students, teachers and practitioners of economics for improving access to Professor Greenhut's many important essays and papers